Prevalence of dengue in febrile patients in Peru: A systematic review and meta-analysis - Darwin A. León-Figueroa; Edwin A. Garcia-Vasquez; Milagros Diaz-Torres; Edwin Aguirre-Milachay; Jean Pierre Villanueva-De La Cruz; Hortencia M. Saldaña-Cumpa; Mario J. Valladares-Garrido (PLoS ONE, 2025)
Background Dengue is an acute febrile illness that is a significant public health problem. Peru is an endemic region for vector-borne diseases such as dengue, zika, and chikungunya, which initially manifest with febrile illness and can complicate differential diagnosis. Therefore, the present study aimed to determine the prevalence of positive results for dengue or dengue antibodies in Peruvian patients with febrile illness using diagnostic tools such as RT-PCR and ELISA NS1, IgM, and IgG. Methods A literature search was conducted in eight databases or search tools (PubMed, Scopus, Embase, Web of Science, ScienceDirect, Google Scholar, Virtual Health Library, and Scielo) until June 9, 2024. Medical Subject Headings (MeSH) terms such as “dengue” and “Peru” were used, together with the free term “febrile illness”, combined using the Boolean operators AND and OR. We included observational studies with a control group of patients with fever but no dengue infection and a non-control group of febrile patients who tested positive for dengue. Pooled estimates and 95% confidence intervals (CI) were calculated using random-effects models. Study quality and risk of bias were assessed using the Joanna Briggs Institute Statistical Meta-Analysis Assessment and Review Instrument. Heterogeneity was assessed using the I2 statistic, and statistical analysis was performed with R version 4.2.3. Results We included 15 observational studies that met the inclusion criteria developed in 10 regions of Peru and published between 2002 and 2022, with a total of 12,355 patients with febrile illness. The pooled prevalence of positive results for dengue or dengue antibodies in these patients was 21% (95% CI: 9%−36%; 2022 participants; 5 studies; I2 = 98%) for IgG ELISA, 16% (95% CI: 11%−21%; 10891 participants; 10 studies; I2 = 97%) for IgM ELISA, 19% (95% CI: 9%−31%; 2086 participants; 5 studies; I2 = 98%) for NS1 ELISA, and 20% (95% CI: 13%−28%; 3107 participants; 9 studies; I2 = 96%) for RNA PCR. Conclusion Our results suggest a high prevalence of positive results for dengue or dengue antibodies among febrile patients in Peru, which varies depending on the diagnostic method used. Despite this variability, the use of accurate diagnostic methods is essential for the early detection and prevention of serious complications. The findings underline the need to strengthen dengue control strategies, improve diagnostic capacity in health centers, and optimize epidemiological surveillance in high-incidence regions. It is recommended that public health policies focus on these key areas for better management of the disease.